Attracting talent from abroad: Malaysia's experience - Thirucelvam, K.; Ahmad, K.Z.; Mat Zin, M. (2008)
Attracting skilled people in science, technology and engineering (S&T) has assumed urgency in today's increasingly knowledge-intensive economy.Countries, both rich and poor, have adopted various strategies to entice top talents in S&T to their shores. This paper describes the initiatives adopted by Malaysia to attract skilled personnel to serve the country. These measures, however, have not met with much success. An account of the findings of recent study to review these initiatives is also given. It is suggested that future initiatives accord more emphasis to developing partnerships between local scientists and their counterparts abroad.